Identification of susceptibility gene mutations associated with the pathogenesis of familial nonmedullary thyroid cancer. Issue 12 (22nd October 2019) - Zhu, Junwei; Wu, Kaile; Lin, Zhangying; Bai, Suwen; Wu, Jing; Li, Peikun; Xue, Haowei; Du, Juan; Shen, Bing; Wang, Huiyin; Liu, Yehai
Abstract: Background: Familial nonmedullary thyroid cancer (FNMTC) accounts for approximately 3%–9% of all thyroid cancers; however, the mechanisms underlying FNMTC remain unclear. Environmental and genetic (especially genetic mutation) factors may play important roles in FNMTC etiology, development, and pathogenesis. Methods: Three affected members, including two first‐degree relatives, and three healthy members of a family with FNMTC were studied. We performed whole‐exome and targeted gene sequencing to identify gene mutations that may be associated with FNMTC pathogenesis. The results were analyzed using Exome Aggregation Consortium data and the Genome Aggregation Database and further validated using Sanger sequencing. Results: Of 28 pivotal genes with rare nonsynonymous mutations found, 7 were identified as novel candidate FNMTC pathogenic genes ( ANO7, CAV2, KANK1, PIK3CB, PKD1L1, PTPRF, and RHBDD2 ). Among them, three genes ( PIK3CB, CAV2, and KANK1 ) are reportedly involved in tumorigenesis through the PI3K/Akt signaling pathway. Conclusion: We identified seven pathogenic genes in affected members of a family with FNMTC. The PI3K/Akt signaling pathway is thought to be closely related to the development of FNMTC, and three of the susceptibility genes identified herein are associated with this pathway. These findings expand our understanding of FNMTC pathogenesis and underscore PI3K/Akt pathology as a potential therapy target. Abstract : We identified 7 pathogenic genes in affected members of a family with FNMTC. The PI3K/Akt signaling pathway is thought to be closely related to the development of FNMTC, and three of the susceptibility genes identified herein are associated with this pathway. These findings expand our understanding of FNMTC pathogenesis and underscore PI3K/Akt pathology as a potential therapy target.